CDApps: integrated software for experimental planning and data processing at beamline B23, Diamond Light Source. (3rd February 2015) - Hussain, Rohanah; Benning, Kristian; Javorfi, Tamas; Longo, Edoardo; Rudd, Timothy R.; Pulford, Bill; Siligardi, Giuliano
<x xml:space="preserve">Abstract</x> The B23 Circular Dichroism beamline at Diamond Light Source has been operational since 2009 and has seen visits from more than 200 user groups, who have generated large amounts of data. Based on the experience of overseeing the users' progress at B23, four key areas requiring the most assistance are identified: planning of experiments and note‐keeping; designing titration experiments; processing and analysis of the collected data; and production of experimental reports. To streamline these processes an integrated software package has been developed and made available for the users. The subsequent article summarizes the main features of the software.